Self-building According to Social Interaction - the Laws of Change &Development - Semiotic Reading - توهامي إيمان (Milev Journal of Research and Studies, 2020)
We have to pause a little at the importance of symbolic interaction of social relations and its role in the formation of the self from its rhetorical, semantic and reference perspective as a system in which the self grows and develops through human cultural and intellectual communication, so this study seeks to monitor the formation of the symbolic pattern of the interacting self in its intense and indicative significance in conveying the meaning Because that depends on activating the senses with the subject projected in it, this paper comes to explain the advantage of social interactions in changing the structural norms of the self at the level of consciousness and feeling, through the semiotics of culture that focus on the cultural milieu as the climate in which the process of communication between the self and its society takes place in The various communication channels it provides, highlighting and its role in crystallizing cultural awareness of the self in its connection to existence, and how it contributes to building a new knowledge and artistic taste in the process of receiving knowledge with which the self interacts, so that the stage of change and crystallization passes as the norms of the final formation of the human personality and the understanding of himself in what surrounds Here, we reveal the effect of interactivity on the power of its semantic production through the symbolic actor between individuals in their daily relationships in terms of its authority. They have to infuse a group of knowledge with the various ideologies that pass with it into their minds as a sender and a receiver at the same time in an unconscious way, so that it becomes part of their cultural formation and a basis for building their judgments about the things, personalities and attitudes that form their future connections